2016
DOI: 10.1017/s0963548316000389
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of 4-Edge Paths in Graphs With Given Edge Density

Abstract: We investigate the number of 4-edge paths in graphs with a fixed number of vertices and edges.An asymptotically sharp upper bound is given to this quantity. The extremal construction is the quasi-star or the quasi-clique graph, depending on the edge density. An easy lower bound is alsoproved. This answer resembles the classic theorem of Ahlswede and Katona about the maximal number of 2-edge paths, and a recent theorem of Kenyon, Radin, Ren and Sadun about k-edge stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Nagy [15] determined the asymptotic value of ex(n, e, P 4 ). Answering a question of his (Question 3 in [15]) in the affirmative, we prove the following theorem. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…Nagy [15] determined the asymptotic value of ex(n, e, P 4 ). Answering a question of his (Question 3 in [15]) in the affirmative, we prove the following theorem. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…To restate the basic one: given a small graph G on v vertices, we would like to know which large graphs H asymptotically maximise N (G, H), the number of unlabelled copies of G in H, where H runs over all graphs on n vertices and edge density β. Interest in this problem was revitalised by its connection with graphons, and subsequently by the work of Nagy [11], who solved it for G = P 4 . Nagy's result is that for P 4 , as for P 2 , the maximiser is first a quasi-star and then a quasi-clique, with the flip occurring this time at β = 0.0865..., instead of 1 2 .…”
Section: Introductionmentioning
confidence: 99%
“…k We also provide an example in Theorem 4.6 of a graph H which for some c ∈ [0, 1] is optimized on neither the quasi-star nor the quasi-clique, disproving a conjecture of Nagy in [12]. To do so, we find a class of graphs and a graph G that does better for c sufficiently small.…”
Section: Introductionmentioning
confidence: 74%
“…This result was later generalized to k-stars, showing that for any c ∈ [0, 1] the number of homomorphisms from the k-star is maximized when G is the quasi-star or quasi-clique for small k [8], and shortly after for all k ≥ 2 [13]. The question was also studied in the case where H is the 4-edge path, and again it was shown that the optimizing graph is always either the quasi-star and quasi-clique for all densities [12]. Using a local move, we show that the maximum is always attained on a threshold graph, a class of graphs containing both the quasi-clique and quasi-star (See Section 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation